Aesthetic correction of anterior teeth disharmony with lithium disilicate veneers: A case report - Rifa, Nur; Rachmudin, Afniati (Hasanuddin University, 2025)
Introduction: The esthetic restoration of anterior teeth is designed to offer a healthy and harmonious smile by correcting patients most significant aesthetic concerns regarding the size, shape, and color of the upper anterior teeth. An excellent alternative for anterior teeth with extensive restorations is lithium disilicate glass ceramic. This case report describes the treatment of anterior teeth due to tooth deformation with Lithium Disilicate veneers to restore aesthetics and function.Case Report: A 35-year-old female patient complained that her maxillary front teeth were unaesthetic and the teeth size was disharmonious. The patient felt that her appearance was disturbed. Intraoral examination of teeth #11, #21 and #22 revealed composite fillings, Teeth #11 and #22 vitality test (+), Teeth #12 and #21 vitality test (-), percussion and palpation tests (-). Diagnosis of teeth #11 and #22 reversible pulpitis, teeth #12 and #21 Previously Treated Teeth. The restoration plan for teeth #11, #12, #21, and #22 was lithium disilicate indirect veneer. The patient was satisfied with the results.Discussion: Lithium disilicate-based veneers have long been used as a strong and durable material for correcting deformities in the anterior teeth. In this case, marginal adaptation was well achieved the colour matched the natural teeth, and the anterior shape appeared symmetrical.Conclusion: Lithium disilicate veneers are indicated for teeth that have faced significant deformation and restoration. This material is employed due to its minimally invasive nature and its transparency and color, which resemble those of natural teeth, resulting in an aesthetically appealing and natural finish.